Synthesis, structure, and magnetic properties of a family of copper(II) complexes and salts of isoquinoline: (Isoquinoline)nCu(X)2 [X = Cl, Br] and (isoquinolinium)2CuX4(H2O)n [X = Cl, Br; n = 0, 1]. (1st June 2018) - Richardson, Alistair D.; Zirkman, Tyler J.; Kebede, Michael T.; Landee, Christopher P.; Rademeyer, Melanie; Turnbull, Mark M.
Graphical abstract: Reaction of Cu(II) halides with isoquinoline in neutral/acidic media produces a family of complexes whose magnetostructural correlations are reported. Abstract: The compounds (iQuin)2 CuX2 (X = Br (1 ), Cl (2 )), (iQuinH)2 CuBr4 ·H2 O (3 ) and two polymorphs of (iQuinH)2 CuCl4 (4, 5 ) (iQuin = isoquinoline) have been prepared and studied via X-ray crystallography and variable temperature magnetic susceptibility measurements. Compound1 crystallizes in the monoclinic space group P 21 /n while3, 4 and5 all crystallize in the triclinic space group P 1 ¯ ). Magnetic susceptibility measurements for1 are best fit by an antiferromagnetic alternating chain model ( J / k B  = −56.6(2) K, J ′/ k B  = 5.1(8) K) although the crystal structure suggests a uniform chain. Compound2 is well described as an isolated uniform antiferromagnetic chain ( J / k B  = −25.6(1) K), while3 agrees well with the antiferromagnetic rectangular model ( J / k B  = −5. 03(2) K, J ′/ k B  = −1.0(1) K). The two polymorphs, 4 and5, exhibit distinctly different behavior as4 is well described by the 2D-square antiferromagnetic layer model ( J / k B  = −4.24(2) K), but5 crystallizes as well isolated magnetic dimers ( J / k B  = −15.8(1) K). Magnetic superexchange is proposed to occur via either the bihalide or two-halide pathways. Finally, compound6, isoquinolinium tribromide, was isolated as a biproduct of the synthesis of3 and was characterized via X-ray diffraction. The formation of the tribromide ion in situ provides support for the mechanism of electrophilic aromatic bromination reactions which have been previously observed in syntheses similar to that of3 .